2020
DOI: 10.3390/catal10111315
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Arylamination Reaction Catalyzed by Polymer Bound 1,3-(Bisbenzimidazolyl) Benzene Co(II) Complex and Generation of Bioactive Adamanate Amines

Abstract: We herein report the preparation and characterization of an inexpensive polymer supported 1,3-bis(benzimidazolyl)benzeneCo(II) complex [PS-Co(BBZN)Cl2] as a catalyst by using the polymer (divinylbenzene cross-linked chloromethylated polystyrene), on which 1,3-bis(benzimidazolyl)benzeneCo(II) complex (PS-Co(BBZN)Cl2) has been immobilized. This catalyst was employed to develop arylamination reaction and robustness of the same reaction was demonstrated by synthesizing various bioactive adamantanyl-tethered-biphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In light of the above aspects, the present Special Issue is mainly focused on the fabrication and fine-tuning of NMs-free metal oxide catalysts by means of advanced synthetic and/or promotional routes. It consists of fourteen high quality papers, involving: a comprehensive review article on the recent advances on the rational design and fine-tuning of ceria-based metal oxide catalysts [5]; two articles on the ceria nanoparticles morphological effects on N 2 O decomposition [14] and CO oxidation [10] over ceria-based binary oxides; two articles on NO decomposition over K-promoted Co-Mn-Al mixed oxides [34,35]; one article on the effect of ceria synthesis methods on the carbon pathways in dry reforming of methane (DRM) over Ni/CeO 2 catalysts [36]; one article on the impact of synthesis procedure and aliovalent doping in Co-Al spinel-type oxides for lean methane combustion [37]; one article on the support effect on the direct conversion of syngas to higher alcohols over copper-based oxides [38]; one article on nanofibrous Ni/Al 2 O 3 catalysts prepared by electrospinning for methane partial oxidation [39]; one article on the influence of precursor compounds on the selective catalytic reduction (SCR) of NO x by NH 3 over FeMgO x oxides [40]; one article on the synthesis and active sites determination of ZrO 2 -supported WO x solid acid catalysts [41]; one article on the synthesis and electrocatalytic performance of RuO 2 nanoparticles [42]; one article on the fabrication and photocatalytic performance of mesoporous frameworks of ZnFe 2 O 4 (ZFO) and MnFe 2 O 4 (MFO) nanoparticles [43]; and one article on the synthesis of polymer supported catalysts for arylamination reaction [44].…”
Section: This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…In light of the above aspects, the present Special Issue is mainly focused on the fabrication and fine-tuning of NMs-free metal oxide catalysts by means of advanced synthetic and/or promotional routes. It consists of fourteen high quality papers, involving: a comprehensive review article on the recent advances on the rational design and fine-tuning of ceria-based metal oxide catalysts [5]; two articles on the ceria nanoparticles morphological effects on N 2 O decomposition [14] and CO oxidation [10] over ceria-based binary oxides; two articles on NO decomposition over K-promoted Co-Mn-Al mixed oxides [34,35]; one article on the effect of ceria synthesis methods on the carbon pathways in dry reforming of methane (DRM) over Ni/CeO 2 catalysts [36]; one article on the impact of synthesis procedure and aliovalent doping in Co-Al spinel-type oxides for lean methane combustion [37]; one article on the support effect on the direct conversion of syngas to higher alcohols over copper-based oxides [38]; one article on nanofibrous Ni/Al 2 O 3 catalysts prepared by electrospinning for methane partial oxidation [39]; one article on the influence of precursor compounds on the selective catalytic reduction (SCR) of NO x by NH 3 over FeMgO x oxides [40]; one article on the synthesis and active sites determination of ZrO 2 -supported WO x solid acid catalysts [41]; one article on the synthesis and electrocatalytic performance of RuO 2 nanoparticles [42]; one article on the fabrication and photocatalytic performance of mesoporous frameworks of ZnFe 2 O 4 (ZFO) and MnFe 2 O 4 (MFO) nanoparticles [43]; and one article on the synthesis of polymer supported catalysts for arylamination reaction [44].…”
Section: This Special Issuementioning
confidence: 99%
“…B. Chumadathil Pookunoth et al [44] reported on the immobilization of a 1,3-bis(benzimidazolyl) benzeneCo(II) complex on divinylbenzene cross-linked chloromethylated polystyrene, as an inexpensive polymer matrix. This particular system was tested on the arylamination reaction and showed robustness in the preparation of bioactive adamantanyl-tethered-biphenylamines.…”
Section: Contribution Highlightsmentioning
confidence: 99%